Neoliomera moana, a new cavernicolous species of xanthid crab from the Marquesas Islands (Crustacea: Decapoda: Brachyura) - Poupin, Joseph; Starmer, John (Zootaxa, 2013)
A new crab Liomerinae, Neoliomera moana sp. nov., is described from the Marquesas Islands, based on three specimens collected by hand at the entrance of submarine caves at depths of 6–28 m. Within the genus the new species belongs to a group of six species that have the carapace cristate on the anterolateral margins. It can be recognized by the presence of a double crest on the upper margin of the palm of chela and by its colour pattern, with about twenty red spots on the dorsal surface of the carapace. This new species is considered has a potential endemic form to the Marquesas Islands.